Evolution of Plant P-Type ATPases - Pedersen, Christian N.; Axelsen, Kristian B.; Harper, Jeffrey F; Palmgren, Michael G. (Frontiers in Plant Science, 2012)
Five organisms having completely sequenced genomes and belonging to all major branches of green plants (Viridiplantae) were analyzed with respect to their content of P-type ATPases encoding genes. These were the chlorophytes Ostreococcus tauria and Chlamydomonas reinhardtii, and the streptophytes Physcomitrella patens (a moss), Selaginella moellendorffii (a primitive vascular plant), and Arabidopsis thaliana (a model flowering plant). Each organism contained sequences for all five subfamilies of P-type ATPases. Our analysis demonstrates when specific subgroups of P-type ATPases disappeared in the evolution of Angiosperms. Na/K-pump related P2C ATPases were lost with the evolution of streptophytes whereas Na+ or K+ pumping P2D ATPases and secretory pathway Ca2+-ATPases remained until mosses. An N-terminally located calmodulin binding domain in P2B ATPases can only be detected in pumps from Streptophytae, whereas, like in animals, a C-terminally localized calmodulin binding domain might be present in chlorophyte P2B Ca2+-ATPases. Chlorophyte genomes encode P3A ATPases resembling protist plasma membrane H+-ATPases and a C-terminal regulatory domain is missing. The complete inventory of P-type ATPases in the major branches of Viridiplantae is an important starting point for elucidating the evolution in plants of these important pumps.